Immunotherapy for neurological diseases - Villoslada, Pablo (Clinical immunology (Orlando, Fla.), 2008)
The burden of neurological diseases in western societies has accentuated the need to develop effective therapies to stop the progression of chronic neurological diseases. Recent discoveries regarding the role of the immune system in brain damage coupled with the development of new technologies to manipulate the immune response make immunotherapies an attractive possibility to treat neurological diseases. The wide repertoire of immune responses and the possibility to engineer such responses, as well as their capacity to promote tissue repair, indicates that immunotherapy might offer benefits in the treatment of neurological diseases, similar to the benefits that are being associated with the treatment of cancer and autoimmune diseases. However, before applying such strategies to patients it is necessary to better understand the pathologies to be targeted, as well as how individual subjects may respond to immunotherapies, either in isolation or in combination. Due to the powerful effects of the immune system, one priority is to avoid tissue damage due to the activity of the immune system, particularly considering that the nervous system does not tolerate even the smallest amount of tissue damage